Probiotics in Obesity Menagement: Mechanisms, Efficacy and Future Directions - Krzyzaniak, Marta; Patrzykąt, Klaudia Martyna; Brynczka, Izabela; Gorzoch-Burduk, Zofia; Puzio, Julia; Marcinkowska, Paula; Nowicka, Ewelina; Popielarska, Kinga; Jezierski, Michał; Wróblewska, Kamila (Journal of Education, Health and Sport, 2025)
Background. Obesity remains one of the most significant global health challenges. However, it may be cured thanks to the microbiota modulation, as it could affect metabolic regulation. Probiotics have emerged as a potential adjunctive strategy supporting weight management and metabolic health. Aim. The aim of the study was to evaluate the effectiveness of selected probiotic strains in obesity management, as well as to analyse the mechanisms through which these strains influence metabolic and anthropometric outcomes. Material and methods. The research was based on a literature review and comparative analysis of randomized controlled trials published before November 2025. The analysis included human studies examining body weight, BMI, waist circumference, visceral fat, and metabolic markers after 8-24 weeks of probiotic supplementation. Results. The findings indicate that certain strains, such as Lactobacillus gasseri, Lactobacillus plantarum, and Bifidobacterium animalis subsp. lactis, demonstrating clinically relevant benefits – reductions in body weight, as well as improved lipid profiles and enhanced insulin sensitivity. However, the effectiveness varies between strains, and the overall impact remains moderate. Conclusions. Probiotic therapy remains as supportive intervention in obesity management, particularly when used alongside standard weight-loss strategies. Further well-designed clinical studies are required to determine optimal strains, dosages, and long-term safety profiles.